Malignant tumors of the digestive system during pregnancy: problems of timely diagnosis - A. Yu. Ralnikova; V. F. Bezhenar; B. V. Arakelyan; N. A. Tatarova; M. A. Kitaeva; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
Currently, the age of primiparous women is increasing, but the risk of cancer, which is sometimes found during gestation, is also increasing. This article discusses the problems of diagnosis and treatment of cancer during pregnancy, which occurs under the guise of gestational complications. Two cases of malignant neoplasms first discovered during pregnancy are described. The first observation illustrates cholangiocarcinoma in a 37-year-old multiparous, and the second is a case of colorectal cancer in a 40-year-old primiparous. The timely identification of such women is an important challenge of the outpatient, which in the future can help maintain the quality of life of the mother and child.